First record of the genus Trichomma Wesmael (Hymenoptera, Ichneumonidae) from Brazil with description of a new species - Onody, Helena Carolina; Penteado-Dias, Angélica Maria (Zootaxa, 2025)
The present study reports the first occurrence of the genus Trichomma (Ichneumonidae, Anomaloninae) in Brazil through the description and illustration of a new species, Trichomma intervalensis sp. nov. This finding expands the known distribution of the genus within the Neotropical region.